Perspectives on area‐based conservation and its meaning for future biodiversity policy. Issue 1 (15th June 2020) - Bhola, Nina; Klimmek, Helen; Kingston, Naomi; Burgess, Neil D.; van Soesbergen, Arnout; Corrigan, Colleen; Harrison, Jerry; Kok, Marcel T. J.
Abstract: During 2021, Parties to the Convention on Biological Diversity (CBD) are expected to meet in Kunming, China, to agree on a new global biodiversity framework aimed at halting and reversing biodiversity loss, encouraging the sustainable use of biodiversity, and ensuring the equitable sharing of its benefits. As the post‐2020 global biodiversity framework evolves, parties to the convention are being exposed to a range of perspectives on the conservation and sustainable use of biodiversity, relating to the future framework as a whole or to aspects of it. Area‐based conservation measures are one such aspect, and there are diverse perspectives on how new targets might be framed in relation to these measures. These perspectives represent different outlooks on the relationship between human and nonhuman life on Earth. However, in most cases there is a lack of clarity on how they would be implemented in practice, the implications this would have for biodiversity and human well‐being, and how they would contribute to achieving the 2050 Vision for Biodiversity of "living in harmony with nature." We sought to clarify these issues by summarizing some of these perspectives in relation to the future of area‐based biodiversity conservation. We identified these perspectives through a review of the literature and expert consultation workshops and compiled them into 4 main groups: Aichi+, ambitious area‐based conservation perspectives, new conservation, and whole‐earth conservation. We found that although the perspectives Aichi+ and whole earth are in some cases at odds with one another, they also have commonalities, and all perspectives have elements that can contribute to developing and implementing the post‐2020 global biodiversity framework and achieving the longer term CBD 2050 Vision. Abstract : Article impact statement: Scaling up area‐based conservation is essential to post‐2020 framework to address the CBD mission to improve the status of biodiversity. Abstract : Perspectivas de la Conservación Basada en el Área y su Significado para las Futuras Políticas de Biodiversidad Resumen: Durante 2021, se espera que las partes miembro del Convenio sobre la Diversidad Biológica (CBD) se reúnan en Kunming, China, para acordar un nuevo marco de trabajo global para la biodiversidad enfocado en detener y revertir la pérdida de la biodiversidad, promover el uso sustentable de la biodiversidad y asegurar la repartición equitativa de sus beneficios. Conforme evoluciona el marco de trabajo global para la biodiversidad post‐2020, las partes miembro del convenio están conociendo una gama de perspectivas de la conservación y el uso sustentable de la biodiversidad, relacionándolas con el futuro marco de trabajo en su totalidad o sólo con algunos aspectos del marco de trabajo. Las medidas de conservación basadas en el área son uno de dichos aspectos y existen diversas perspectivas sobre cómo los nuevos objetivos podrían estar enmarcados en relación a estas medidas. Estas perspectivas representan diferentes puntos de vista sobre la relación entre la vida humana y no humana en la Tierra. Sin embargo, en la mayoría de los casos existe una falta de claridad sobre cómo se implementarían en la práctica, las implicaciones que ésto tendría para la biodiversidad y el bienestar humano y cómo contribuirían para alcanzar la Visión para la Biodiversidad 2050 de "vivir en armonía con la naturaleza". Buscamos aclarar estos temas al resumir algunas de estas perspectivas en relación al futuro de la conservación de la biodiversidad basada en el área. Identificamos estas perspectivas por medio de una revisión de la literatura y talleres de consulta a expertos y las compilamos en cuatro grupos principales: Aichi+, perspectivas ambiciosas de conservación basada en el área, conservación nueva y conservación del mundo entero. Descubrimos que aunque las perspectivas Aichi+ y conservación del mundo entero entran en conflicto en algunos casos, también tienen puntos comunes, y todas las perspectivas tienen elementos que pueden contribuir al desarrollo e implementación del marco de trabajo global para la biodiversidad post‐2020 y para alcanzar la Visión CBD 2050 de mayor plazo. 摘要: 《生物多样性公约》缔约方将于 2021 年底在中国昆明举行会议, 就全球生物多样性的新框架达成一致, 该框架旨在制止和扭转生物多样性丧失、鼓励可持续利用生物多样性、确保公平和公正分享遗传资源所产生的惠益。随着 2020 后全球生物多样性框架的发展, 公约的缔约方接触到了生物多样性保护和可持续利用的一系列观点, 涉及未来框架的整体或其各个方面。而在基于区域的保护措施这个方面, 人们对如何制定相关新目标持有不同观点。这些观点代表了对地球上人类和非人类生命之间关系的不同看法。然而, 在大多数情况下, 如何实践这些观点、它们对生物多样性和人类福祉有何影响, 以及它们将如何帮助实现 "与自然和谐相处"的 2050 生物多样性愿景, 都缺乏明确的说明。我们试图通过总结与区域生物多样性保护的未来相关的一些观点来阐明这些问题。我们通过文献综述和专家咨询研讨会确定了这些观点, 并将它们分为 4 个主要的类别:爱知+、具有雄心的区域保护观点、新的保护观点和保护整个地球的观点。我们发现, 虽然"爱知+"和"保护整个地球"的观点在某些情况下不能取得一致, 但它们也有共同点, 并且都具有帮助制定和实施 2020 后全球生物多样性框架和实现《生物多样性公约》 2050 长期愿景的因素。 【翻译: 胡怡思; 审校: 聂永刚】